2021
DOI: 10.21203/rs.3.rs-415931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioremoval mechanisms of azo dye Acid Red 14 using Wickerhamomyces anomalus yeast strain as a natural biosorbent

Abstract: Biosorption processes have recently become an economic and eco-friendly solution for the treatment of industrial wastewater. This study aimed to evaluate the potential application of Wickerhamomyces anomalus as a natural biosorbent for the removal of toxic synthetic dye Acid Red 14 (AR14). Biosorption kinetics modelling showed that the pseudo-second-order and intraparticle diffusion models were more suitable to fit the experimental data. In addition, the Langmuir model was the most appropriate isotherm to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Due to the peptide bonds of the yeast cell, the amide I and amide II bands were visible in the spectrum between 1700 and 1500 cm −1 (presence of -C=O and N-H functional groups at 1672.21 and 1654.63 cm −1 , respectively). Peaks were observed in yeast at 1538.92 cm −1 and in dye-adsorbed yeast at 1537.95 cm −1 , corresponding to C=C stretching of aromatic rings [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the peptide bonds of the yeast cell, the amide I and amide II bands were visible in the spectrum between 1700 and 1500 cm −1 (presence of -C=O and N-H functional groups at 1672.21 and 1654.63 cm −1 , respectively). Peaks were observed in yeast at 1538.92 cm −1 and in dye-adsorbed yeast at 1537.95 cm −1 , corresponding to C=C stretching of aromatic rings [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the type of interaction between the adsorbent surface and the contaminant, the biosorption process can be divided into two types: (i) chemical adsorption, an irreversible process resulting in the formation of strong chemical bonds; and (ii) physical adsorption, which is reversible and, in most cases, characterized by weak van der Waals forces, H-bonds, polarity and dipole–dipole H-bonding interactions. Furthermore, FTIR studies have demonstrated that Yoshida H-bonding, dipole–dipole H-bonding and π–π and n–π interactions can occur upon adsorption of dye molecules on yeast cells ( Figure 6 ) [ 32 , 35 , 61 ].…”
Section: Resultsmentioning
confidence: 99%